Transcatheter aortic valve implantation outcomes compared between bicuspid aortic and tricuspid aortic valve stenosis: an updated systematic review and meta-analysis. (14th October 2021) - Aedma, S; Gupta, R; Mahajan, S; Mahajan, P; Patel, M; Malik, A; Naik, A; Mehta, S; Patel, N C
Abstract: Background: TAVI has emerged as an attractive treatment modality based on promising recent trial data. Patients with BAV, a commonly encountered clinical condition have largely been excluded from a majority of trials. Purpose: Elderly patients with BAV and severe AS are increasingly encountered in clinical practice. This meta-analysis compares clinical outcomes between bicuspid and tricuspid AV patients to address the current knowledge-gap and identify optimal management strategies of these patients. Methods: A comprehensive literature search was performed in PubMed, Embase, and Cochrane to identify the available observational studies comparing outcomes of TAVI in BAV and TAV patients. Summary effects were calculated using a DerSimonian and Laird random-effects model as odds ratio with 95% confidence intervals for all the clinical endpoints. Results: 16 Observational studies met inclusion criteria, comprising 10, 053 patients with BAV and 173, 307 patients with TAV that underwent TAVI. No significant differences in 30-day and long-term mortality rates were observed. Patients with BAV had an increased risk of stroke (OR 1.23; 95% CI [1.06–1.44], p=0.007), re-intervention (OR 1.90; 95% CI [1.15–3.15], p=0.01), paravalvular leak (OR 1.42; 95% CI [1.25–1.61], p<0.ehab724.22251), conversion to open surgery (OR 1.93; 95% CI [1.21–3.07], p=0.006), and new pacemaker implantation (1.57; 95% CI (1.06 - 2.33, p=0.02). Adverse event rates are lower with the use of newer generation of valves. No significant difference in major vascular complications, major bleeding, or incidence of AKI was noted. Conclusions: Complication rates for BAV TAVI are higher, but mortality is similar to TAV TAVI indicating TAVI is an appropriate alternative for intermediate-high risk patients with BAV. A better understanding of valve anatomy, physician expertise, the use of newer-generation valves can help reduce these complications. Funding Acknowledgement: Type of funding sources: None.